Usage Analysis of Irrigation Water of Red Rice Cultivation with Legowo Nyisip Cropping Systems (Case Studies in Subak Sigaran) - Dipayana, I Komang Adi; Tika, I Wayan; Sumiyati, Sumiyati (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
This researce is conducted to compare the usage of irrigation water of red rice cultivation by using legowo nyisip planting sytem and compare productivity of the treatments. This research was consist of five treatments, they were: K0 (the treatment which appropriate to local farmers custom), K1 (planting system of legowo 4:1), K2 (planting sytem of legowo 4:1 nyisip), K3 (planting sytem of legowo 6:1), K4 (planting system of legowo 6:1 nyisip). Parameters that observed in this research were: the requirement of irrigation water, the efficiency of irrigation water using, the number of plants produce grains, the stalks length, the weight of rice in a clump, the rice weight per clump, the percentage of rice based on its amount, the percentage of rice based on its weight, the weight of 1000 grains and the result rice plants production. The research results showed significant differences with cultivation technique between the treatments was no influence to the requirement of irrigation water and efficiency relative in every treatments. To productivity KO produced 5.4 ton/ha, K1 produced 7.8 ton/ha, K2 produced 7:2 ton/ha, K3 produced 7:7 ton/ha, and K4 produced 6:5 ton/ha.